Effects of fecal microbiota transplantation with oral capsules in obese patients - Allegretti,JR; Kassam,Z; Mullish,BH; Chiang,A; Carrellas,M; Hurtado,J; Marchesi,JR; McDonald,JAK; Pechlivanis,A; Barker,GF; Miguens,Blanco J; Garcia,Perez I; et al. (Clinical Gastroenterology and Hepatology, 2020)
Background & AimsStudies in mice have shown that the intestinal microbiota can contribute to obesity via the anorexigenic gut hormone glucagon-like peptide 1 (GLP1) and bile acids, which affect lipid metabolism. We performed a randomized, placebo-controlled pilot study of the effects of fecal microbiota transplantation (FMT) in obese, metabolically uncompromised patients.MethodsWe performed a double-blind study of 22 obese patients (body mass index [BMI] ≥ 35kg/m2) without a diagnosis of diabetes, non-alcoholic steatohepatitis, or metabolic syndrome. Participants were randomly assigned (1:1) to groups that received FMT by capsules (induction dose of 30 capsules at week 4 and maintenance dose of 12 capsules at week 8) or placebo capsules. FMT capsules were derived from a single, lean donor (BMI, 17.5 kg/m2). Patients were followed through week 26; the primary outcome was safety. Stool and serum samples were collected from patients at baseline and at weeks 1, 4, 6, 8 and 12 after administration of the first dose of FMT or placebo and analyzed by 16S RNA gene sequencing. Stool and serum samples were analyzed for metabolomics by liquid chromatography-mass spectrometry. Additional outcomes were change in area under the curve for GLP1 at week 12.ResultsWe observed no significant differences in adverse events between patients who received FMT vs placebo. There was no increase in the area under the curve of GLP1 in either group. Patients who received FMT had sustained shifts in microbiomes associated with obesity toward those of the donor (P<.001). Patients who received FMT had a sustained decrease in stool levels of taurocholic acid (P<.05), compared with baseline; bile acid profiles began to more closely resemble those of the donor. We did not observe significant changes in mean BMI at week 12 in either group.ConclusionsIn a placebo-controlled pilot study, we found that FMT capsules (derived from a lean donor) were safe but did not reduce BMI in obese metabol